2010
DOI: 10.1002/pits.20503
|View full text |Cite
|
Sign up to set email alerts
|

Children's self‐regulated learning profile in language and mathematics: The role of task value beliefs

Abstract: This study explored the self-regulated learning (SRL) profile of upper elementary (fifth and sixth grade) school children who were differentiated in their task value beliefs (low and high) in language and mathematics. Students' SRL profile involved their teachers' ratings of achievement outcomes and SRL behaviors. The subscale of task value beliefs from the Motivational Self-Regulated Learning Questionnaire (MSLQ) was administered to the children, and their teachers completed a battery of scales and measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 42 publications
0
26
0
8
Order By: Relevance
“…Other studies indicate that positive changes in task values can improve affect and academic achievements in mathematics in self-regulated learning environments (e.g. Metallidou & Vlachou, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies indicate that positive changes in task values can improve affect and academic achievements in mathematics in self-regulated learning environments (e.g. Metallidou & Vlachou, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…From the perspective of these theories, it can be assumed that students' motivation to learn is influenced by the importance attributed to learning and its objects (Wigfield & Eccles, 1992, 2000. Metallidou and Vlachou (2010) show that students with high value beliefs in mathematics are described by teachers in self-regulated learning environments as better learners in the cognitive, metacognitive and motivational domains.…”
Section: Values and Interestmentioning
confidence: 99%
“…Similarly to previous studies that used students of that age (Metallidou & Vlachou, 2010) three aspects of fifth and sixth grade students' learning strategies as outlined by Pintrich and De Groot (1990) were assessed. Specifically, students' were asked to report on a 5-point Likert-type scale ranging from 1 (Not at all true of me) to 5 (Very true of me) to what extent they (a) recruit critical thinking (5 items; e.g., "I often find myself questioning things I hear or read in this course to decide if I find them convincing"; α = .69), (b) employ metacognitive self-regulation (5 items; e.g., "When I become confused about something I'm reading for my class, I go back and try to figure it out"; α=.61), and (c) regulate their effort in an efficient way (3 items; e.g., "I work hard to do well in this class even if I don't like what we are doing"; α=.65).…”
Section: Motivated Learning Strategiesmentioning
confidence: 99%
“…Particularly the studies of secondary education have shown that SRL factors predict academic achievement (Wolters, 1999) because of autonomy of learning as well as increased contextual complexity. Besides, there have been many studies of SRL which indicated that students equipped with higher level of knowledge and effective use of SRL strategies have been successful in obtaining higher literacy abilities (Schunk & Zimmerman, 2007), mathematics (Metallidou & Vlachou, 2010;Belal-Rabab'h & Arsaythamby, 2015), and science skills (Cleary et al, 2008).…”
Section: Self-regulated Learning (Srl)mentioning
confidence: 99%